Telosticta fugispinosa sp. nov. from Sabah (Odonata: Zygoptera: Platystictidae) - Dow, Rory A.; Afendy, Aqilah; Rahman, Homathevi (Zootaxa, 2016)
Telosticta fugispinosa sp. nov. (holotype male, from Borneo, Sabah, West Coast division, Crocker Range National Park, Inobong, Kimamabang waterfall stream system, 21 ix 2012, deposited in RMNH) is described from Kinabalu National Park and Crocker Range National Park in Sabah, Malaysian Borneo. It is distinguished from all other species of Telosticta by the form of the male anal appendages.